1979
DOI: 10.1002/ajmg.1320030209
|View full text |Cite
|
Sign up to set email alerts
|

An examination of the spectrum of anatomic defects and variations found in eight cases of trisomy 13

Abstract: We report the anatomic variations found in four additional cases of trisomy 13. Data from these and four previous cases [Colacino and Pettersen, 1978] are utilized to define a muscle phenotype. Previously unreported defects include the bilateral presence of cervical ribs and the bilateral absence of 12th thoracic ribs in five of the eight cases. One unusual developmental defect of the great vessels is also described. The findings suggest that a definitive diagnosis of trisomy 13 can be made on the basis of six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

1979
1979
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 14 publications
(5 reference statements)
1
16
0
1
Order By: Relevance
“…To our knowledge, there has been no previous mention of any involvement of the thalamus and basal ganglia in studies dealing with anatomic defects and microscopic craniofacial anomalies in trisomy 13 patients [Pettersen et al, 1979;Sperber et al, 1989]. Perhaps this mineralizing vasculopathy with possible vascular compromise of the thalamus and basal ganglia may be a contributory factor to the poor outcome of these infants.…”
Section: Discussionmentioning
confidence: 79%
“…To our knowledge, there has been no previous mention of any involvement of the thalamus and basal ganglia in studies dealing with anatomic defects and microscopic craniofacial anomalies in trisomy 13 patients [Pettersen et al, 1979;Sperber et al, 1989]. Perhaps this mineralizing vasculopathy with possible vascular compromise of the thalamus and basal ganglia may be a contributory factor to the poor outcome of these infants.…”
Section: Discussionmentioning
confidence: 79%
“…The majority of these abnormal structures appear in the forelimb. Trisomy 13 has been characterized anatomically by the presence of a pectorodorsalis muscle, which is not normally seen in humans but is found in many nonhuman primates, and by reduction and absence of several muscles in the forelimb, including particularly absence of the palmaris longus and brevis, and absence or variation of the extensor indicis [Pettersen et al, 1979] (Table II). The reduction or absence of muscles has been interpreted as being related to their normal appearance late in development or to excessive resorption of muscle tissue when the deep and superficial layers are forming [Dunlap et al, 1986].…”
Section: Discussionmentioning
confidence: 99%
“…The findings in the trisomic infant include the presence of a supernumerary postaxial digit bilaterally, absence of the palmaris longus and brevis bilaterally, and in the right forelimb, presence of accessory slips of muscle between the flexor digitorum superficialis and profundus, between the tendon of the extensor pollicis longus and the extensor digitorum proprius, and from the first lumbrical to the first digit in addition to the normal insertion into digit II. Pettersen et al [1979] suggested that the identification of trisomy 13 can be based on six muscle variations, four of which occur in the forelimb: presence of the pectorodorsalis muscle, absence of the palmaris longus and brevis muscles, and absence or variation of the extensor indicis muscle. Presence of the pectorodorsalis muscle in humans is an example of an atavistic muscle discussed by Dunlap et al [1986], whereas absence of the palmaris longus and brevis and variation of the extensor indicis is observed not infrequently in nonhuman primates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies of the skeletal phenotype in trisomy 13 the anomalies most commonly described are wide anterior fontanelle, presence of a cervical rib, absence of the 12th rib, anomalies of rib morphology, low acetabular angles, and long distal phalanges [Patau et al, 1960;Mottet and Jensen, 1965;Snodgrass et al 1966;Taylor, 1968;Colacino and Pettersen, 1978;Pettersen et al, 1979;Jacobs et al, 1987;Keeling, 1994]. Malformations of the fifth finger and toe are frequent, and polydactyly has also been reported [Opitz et al, 1979;Gilbert and Opitz, 1982].…”
Section: Introductionmentioning
confidence: 99%